2020
DOI: 10.1177/2045894019880086
|View full text |Cite
|
Sign up to set email alerts
|

Medication adherence, hospitalization, and healthcare resource utilization and costs in patients with pulmonary arterial hypertension treated with endothelin receptor antagonists or phosphodiesterase type‐5 inhibitors

Abstract: Adherence to therapy for pulmonary arterial hypertension is essential to optimize patient outcomes, but data on real-world adherence to different pulmonary arterial hypertension drug classes are limited. This retrospective database analysis evaluated relationships between adherence, hospitalization, and healthcare costs in pulmonary arterial hypertension patients treated with endothelin receptor antagonists or phosphodiesterase type-5 inhibitors. From the IQVIA Adjudicated Health Plan Database, patients with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 34 publications
10
32
0
1
Order By: Relevance
“…High costs or co-payments for treatment and healthcare have been shown to contribute to poor medication adherence [ 17 , 27 ]. However, in the present study there was no relation between socioeconomic factors and adherence, despite the household income being at, or slightly lower than, the average disposable income in Sweden.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High costs or co-payments for treatment and healthcare have been shown to contribute to poor medication adherence [ 17 , 27 ]. However, in the present study there was no relation between socioeconomic factors and adherence, despite the household income being at, or slightly lower than, the average disposable income in Sweden.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic treatment (≥3 filled prescriptions/year) Angiotensin converting enzyme inhibitors 108 (19) 81 2127 (14) Angiotensin-receptor blockers 101 (18) 65 (17) 36 (19) Beta Asthmainhaler therapy 171 (30) 119 (31) 52 (28) Anti-diarrheal drugs 79 (14) 62 (16) 17 (9) Anti-emetics 61 (11) 52 (14) 9 (5) Anti-acid drugs 47 (8) 41 (11) 6 (3)…”
Section: All Pah Cteph N=571 N=384 N=187mentioning
confidence: 99%
“…So far, several lines of evidence have strongly suggested that targeting the NO pathway might be the strategy with the most potential. A recent investigation also found that higher adherence to PDE5 in patients with PAH is associated with a lower risk of hospitalization and rehospitalization (48). Therefore, we suggest the following for further research: (I) conducting high-quality studies at the recommended dose of 20 mg/TID; (II) trials should measure outcomes which are clinically relevant (e.g., mortality, quality of life, and clinical worsening) so that the long-term effects can be established; and (III) attach importance to the real-world data and evaluation of pharmacoeconomics.…”
Section: Discussionmentioning
confidence: 91%
“…Individuals were considered adherent if they achieved PDC ≥80%, a standard threshold for pharmacologic adherence in PAH and other conditions. 24 , 25 Those using combination therapy were not included in adherence analyses for ERAs or PDE5.…”
Section: Methodsmentioning
confidence: 99%